2008
DOI: 10.1177/0731684408090714
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Co-Infusion as a Viable Method for In-Mold Coating of Composite Components

Abstract: This work assessed the viability of co-infusing a thermoset resin and liquid coating formulations for the in-mold coating of composite components manufactured by the resin infusion between double tooling (RIDFT) process. Material trade studies conducted to resolve the compatibility issues of the separation layer and coating material were successful. The modifications of the RIDFT-IMC assembly succeeded in eliminating the risk of premature fiber wetting during coating material infusion. Experiments were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Infusion of the matrix resin at the same time as a polyurethane enamel paint (DuPont Imron 5000), coating layer in the same flexible mould (Chiu and Okoli, 2006;Thagard et al, 2004;Chiu, 2004) was suggested for potential development if an appropriate separation layer could be developed. Solomon (2009) enhanced the separation of the two fluids by eliminating the use of a single vacuum flow path for the coating and the resin. Similarly, a technique using thermo formable paint films (Toro et al, 2005) was proven to be viable but needed further development of the paint film, allowing it to fully adhere within the resin gel time at elevated temperatures.…”
Section: Resin Infusion Under Double Flexible Tooling (Ridft)mentioning
confidence: 99%
“…Infusion of the matrix resin at the same time as a polyurethane enamel paint (DuPont Imron 5000), coating layer in the same flexible mould (Chiu and Okoli, 2006;Thagard et al, 2004;Chiu, 2004) was suggested for potential development if an appropriate separation layer could be developed. Solomon (2009) enhanced the separation of the two fluids by eliminating the use of a single vacuum flow path for the coating and the resin. Similarly, a technique using thermo formable paint films (Toro et al, 2005) was proven to be viable but needed further development of the paint film, allowing it to fully adhere within the resin gel time at elevated temperatures.…”
Section: Resin Infusion Under Double Flexible Tooling (Ridft)mentioning
confidence: 99%
“…Different from traditional RTM process like RIDFT (Resin Infusion between Double Tooling), this method uses two sets of RTM injection systems to inject two distinctive types of resin independently and simultaneously into the mold, which is filled with fiber preform and vacuumized beforehand. 1519 This course is called “co-injection”, whose detailed illustration is as shown in Figure 2. Fiber preform A and fiber preform B made from carbon fiber plain fabrics refer to two preforms used to make the carbon/epoxy layer and carbon/phenolic layer of the sandwich panel.…”
Section: Manufacture Processingmentioning
confidence: 99%
“…Apart from conventional coating or painting a component after being moulded, other alternatives of coating include applying the corresponding coat onto the mould before placing the preform [275], injecting the coat between the mould and the components after being moulded [279], placing a thermoformable film between the preform and the mould [280,281], and coinfusing the coat and the matrix [282][283][284]. The last three listed procedures would be compatible with ISFLIP, being the thermoformable film method a specially interesting technology to be combined with.…”
Section: Look and Feel And Roughnessmentioning
confidence: 99%